In Vitro Propagation Of Vanilla (Vanilla Planifolia Andr.) On Different Concentration Of Cytokinins - Sitti Inderiati; Ratnawati Ratnawati; Since Since (Jurusan Budidaya Tanaman Perkebunan, Politeknik Pertanian Negeri Pangkajene Kepulauan, 2019)
Micropropagation of vanilla was conducted through excised apical shoot tip and nodal segment as explants to determine the best concentration of growth hormone of cytokinin on multiple shoots production and regeneration. The explants were cultured on MS medium augmented with different concentration of N6-Benzyladenin and Kinetin. Sub culture was done four weeks after inoculation to regenerate more elongated shoots on the medium containing the same concentration of plant growth regulators as inoculation medium. After 60 days of cultured, multiple regenerated shoots were elongated and formed leaves and roots. The two cytokinins tested induced bud break to different degrees. Among the various concentrations tested N6-Benzyladenin at 1.5 mg.l-1 gave the highest mean shoot number (3.27/explant) and leaves (3.80/shoot) differentiation. While the lowest number of shoots and leaves were found on MS medium fortified with 1.0 mg.l-1 Kinetin. All cultures produced roots and the highest number of roots formed on the medium containing 2 mg.l-1 Kinetin.